1988
DOI: 10.1111/j.1748-5827.1988.tb02293.x
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Chlamydia psittaci in different cat populations in Britain

Abstract: The prevalence of Chlamydia psittaci infection in household, feral and farm cats in Britain was investigated. Chlamydia were isolated from 30 per cent of conjunctival swabs collected from 753 household cats with conjunctivitis. The prevalence of active chlamydial infection was highest in cats in the age group five weeks to nine months. Males were more frequently infected than females. Cats with chlamydial conjunctivitis usually had antibody titres greater than 1024 as assessed by indirect immunofluorescence. C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

9
48
3
2

Year Published

2000
2000
2024
2024

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 57 publications
(62 citation statements)
references
References 13 publications
9
48
3
2
Order By: Relevance
“…They all typically suffered from conjunctivitis, and the second most frequent clinical sign was rhinitis found in 6 cats. The present prevalence rate (26.9%) was as high as those reported in Australia [28], Britain [16,29], Canada [14], Japan [6,21], New Zealand [7], and the U.S. [19] where cats with the URI or ocular disease were subjects of investigation. In contrast, the prevalence in healthy cat population was relatively low [8].…”
supporting
confidence: 52%
“…They all typically suffered from conjunctivitis, and the second most frequent clinical sign was rhinitis found in 6 cats. The present prevalence rate (26.9%) was as high as those reported in Australia [28], Britain [16,29], Canada [14], Japan [6,21], New Zealand [7], and the U.S. [19] where cats with the URI or ocular disease were subjects of investigation. In contrast, the prevalence in healthy cat population was relatively low [8].…”
supporting
confidence: 52%
“…In relation to the comparison of the two serological techniques, our data corroborate previous reports (Wills et al 1988, Griffiths et al 1996, Markey et al 1993) that compared IFA with CFT, showing that CFT is specific (100%), but it is not a sensitive (9.5%) method to search for anti-Chlamydophila spp antibodies in domestic cats, since cats showing IFA titers greater than 1024 may not have detectable complement-fixation antibodies to Chlamydia. Predictive values suggest that IFA can be used in routine testing and research procedures.…”
Section: Virus Reviews and Research 15 Nr 2 2010supporting
confidence: 80%
“…However, in England and Sweden, only 9.1% and 11% of the animals, respectively, were IFA-positive (Gunn-Moore et al 1995, Holst et al 2006. Among unvaccinated cats with clinical signs (G2), 68.89% (31/45) were IFApositive, as also reported by Wills et al (1988), who found 60% (69/116) of IFA-positive animals. In unvaccinated cats, paired serology in IFA can confirm diagnosis of C. felis infection.…”
Section: Virus Reviews and Research 15 Nr 2 2010supporting
confidence: 59%
See 1 more Smart Citation
“…Our previous seroepidemiological surveys indicated that the prevalence rates of feline chlamydiosis were 2.1 to 34.4% in Japan (7,18). The prevalences in other countries have been variously reported to be 5.3 to 69% (5,11,30). Circumstantial evidence indicated that human beings may be infected with feline C. psittaci and develop conjunctivitis (22) and serious systemic infection (19).…”
mentioning
confidence: 99%